Students' Understanding of Government Regulations in TransactionsShopee E-Commerce - yadi, Hendri; Asriani; Hanif; Moh Mukri; Sitti Aminah Baharuddin (Universitas Islam Negeri Raden Intan Lampung, 2025)
The rapid development of e-commerce has transformed student consumption behavior, with Shopee becoming one of the most popular platforms due to its ease and speed of service. However, despite this convenience, many users still do not understand their rights as consumers, particularly regarding product authenticity, refund policies, and personal data privacy. This study aims to analyze students' level of understanding of government regulations regarding consumer protection in transactions on the Shopee platform. The method used was descriptive qualitative, with data collected through surveys and in-depth interviews with one hundred active Shopee student users from four universities in Bandar Lampung. The results showed that only 30% of respondents had a good understanding of consumer protection policies, while the other 70% still had little understanding. These findings indicate low legal and digital literacy among students as digital consumers, which makes them vulnerable to fraud and unfair business practices. This study concludes that improving digital and legal literacy for consumers is necessary to enable them to protect their rights independently. In addition, the government and e-commerce platforms need to strengthen regulations, public education, oversight, and collaboration in creating a fair and secure digital transaction ecosystem.